2019
DOI: 10.13005/ojc/350103
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Mechanisms of Nitro Compounds Reduction (A-Review)

Abstract: The article describes some variants of mechanisms of nitro compounds reduction, offered by authors in the scientific literature. The focus is on the description of the work of Kazakh and Russian chemists working in the field of catalysis. In most of the works, the classical scheme of the mechanism of the hydrogenation of Haber-Lukashevich nitrobenzene is confirmed and detailed by experimental methods. One of the interesting aspect of the article is description the mechanism of Ya.A. Dorfman which used the orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In addition, it can be observed that the presence of electron-donating group (-NH 2 ) led to decrease of the yield of the reaction due to the stabilization of resonance effects to the nitro functionality 54 . According to the literature, in the case of halogen substituted reagent, dehalogenation may be responsible for low yield 55 . www.nature.com/scientificreports www.nature.com/scientificreports/ In the following, the effects of carbonization of MT, Glu shell and Hal etching on the catalytic activity were studied.…”
Section: Results and Discussion Catalyst Characterization The Xrd Patmentioning
confidence: 99%
“…In addition, it can be observed that the presence of electron-donating group (-NH 2 ) led to decrease of the yield of the reaction due to the stabilization of resonance effects to the nitro functionality 54 . According to the literature, in the case of halogen substituted reagent, dehalogenation may be responsible for low yield 55 . www.nature.com/scientificreports www.nature.com/scientificreports/ In the following, the effects of carbonization of MT, Glu shell and Hal etching on the catalytic activity were studied.…”
Section: Results and Discussion Catalyst Characterization The Xrd Patmentioning
confidence: 99%
“…DAS can be used to produce phosphorescent whiteners for fibers and paper. Catalysts based on supported palladium catalysts with the addition of platinum and rhodium showed high selectivity during hydrogenation during the reduction of both nitro groups and the aromatic ring in nitrobenzene using isopropanol and ethanol as solvents [2,3,8]. The role of palladium in catalytic reactions is largely determined by the different structure of active sites on its surface.…”
Section: -5286mentioning
confidence: 99%
“…Despite the high cost, the catalysts based on platinum group metals are widely used in the hydrogenation of organic compounds, in particular, for the production of aromatic amines from the corresponding nitro compounds. A special role in this is played by the catalysts of the platinum group deposited on various carriers [8,14]. The reduction of 3,4-dichloronitrobenzene in the presence of iridium and platinum catalysts was studied and it was established that the limiting stage of the process is the step of converting the corresponding arylhydroxylamine into an amino compound.…”
Section: -5286mentioning
confidence: 99%
“…However, materials with such a damaged graphene backbone are poor conductors and subjected to rapid degeneration. In the same time, the rich chemistry of nitro compounds (especially a large number of possible reduced forms) [22] encourage great potential in the RedOx applications of graphene with covalently bonded nitro groups.…”
Section: Introductionmentioning
confidence: 99%